Pengaruh Manajemen Sumber Daya Manusia Terhadap Produktivitas Peternakan Sapi Perah - Alfiansyah, Alfiansyah; Erniawati, Erniawati (CV. SINAR HOWUHOWU, 2024)
This study aims to analyze the effect of Human Resource Management (HRM) on the productivity of dairy farms in Indonesia. Given the importance of quality human resource management in the livestock sector, this study explores how training, work motivation, and livestock health management can contribute to increased productivity. Data were collected through a survey involving dairy farmers, and analysis was conducted using statistical methods to measure the relationship between the variables studied. The results showed that good HR management plays a significant role in improving operational efficiency and dairy product quality. Training variables were shown to improve farmers' skills, while high work motivation contributed to improved employee performance. In addition, effective animal health management, including the management of reproductive disorders, has a direct effect on animal health and milk productivity. This study emphasizes the need for a comprehensive approach to human resource management and animal health to achieve optimal productivity in the dairy farming industry. Recommendations for stakeholders include the development of continuous training programs and the creation of a supportive work environment to improve farmer performance. Thus, the results of this study are expected to be a reference in efforts to improve the competitiveness of the dairy farming sector in Indonesia.